Techno‐economic assessment of the effect of torrefaction on fast pyrolysis of pine. (8th January 2016) - Winjobi, Olumide; Shonnard, David R.; Bar‐Ziv, Ezra; Zhou, Wen
Abstract: Techno‐economic assessment of bio‐oil production from fast pyrolysis of pine was explored through process simulation. In this work, bio‐oil production via a one‐step pyrolysis route and a two‐step pyrolysis which included a torrefaction step before fast pyrolysis were modeled to process 1000 MT/day of dry feed (dry basis) through the pyrolyzer at a temperature of 530 °C while two‐step ‐pyrolysis was investigated at three different torrefaction temperatures of 290, 310, and 330 °C. Different scenarios that included the use of fossil energy to produce process heat as well as use of renewable energy either through the combustion of char or a portion of the condensates from ‐torrefaction were also investigated. Economic analysis indicates that a torrefaction step results in a reduction in the minimum selling price of bio‐oil produced which reduced further with ‐torrefaction ‐temperature with lowest bio‐oil price of 1.04/gal obtained for a two‐step pyrolysis at torrefaction ‐temperature of 330 °C in comparison to 1.32/gal for a one‐step process. Minimum selling price of bio‐oil on an energy basis however suggests a higher price of about 22.19/GJ for a two‐step in ‐comparison to 16.89/GJ for a one‐step. There could be a trade‐offs between the higher quality and the higher selling price considering the downstream upgrade step to hydrocarbon fuel. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd